Lepeophtheirus salmonis: a persisting challenge for salmon aquaculture. (1st January 2014) - Igboeli, Okechukwu O.; Burka, John F.; Fast, Mark D.
Abstract: Effective control of parasitic sea lice (including Lepeophtheirus salmonis and Caligus elongatus ) is a major challenge currently facing sea cage salmon aquaculture. This difficulty is linked to widespread resistance to different classes of drugs employed by salmon farmers to control the copepod. Due to drug selective pressure leading to treatment failure, sole reliance on parasiticides can only serve as short-term solutions for the control of sea lice. For effective sea lice management in salmon farms, there is a need to combine drug rotations with non-chemical strategies.